HOW THE DRAGON GOT TWO TONGUES: ENGLISH VICTORIAN VALUES AND THE EMERGENCE OF WELSH LITERATURE WRITTEN IN THE ENGLISH LANGUAGE - Fear, Alan Peter (Organon, 2018)
The genesis of a Welsh literature written in the English language can be found in the turbulent middle ages, from the earliest Anglo-Saxon settlements on the island of Britain, to the Norman invasion and occupations of the late Medieval period. However, the emergence of this body of literature, sometimes referred to as Anglo-Welsh writing, can be attributed to many socio-political factors and events of the Victorian Age. At the apex of the British Empire the English educational system was implemented in Wales and an industrialization process meant that thousands of foreign immigrants were effectively diluting the native population driving the Welsh language and ancient culture to near extinction and promoting the use of the English language. As a consequence, Anglo-Welsh writing emerged fully towards the end of the 19th century to the beginning of the 20th century. KEYWORDS: Anglo-Welsh literature, Wales, Culture